Prevalence and factors associated with stroke risk factors in an urban community of Parakou, Northern Benin, 2016 - Yessito Corine Nadège Houehanou; Mendinatou Agbetou; Oyéné Kossi; Maurice Agonnoudé; Hospice Hountada; Thierry Adoukonou (PLOS Global Public Health, 2022)
Sub-Saharan Africa faces a heavy burden of stroke due to the growth of its risk factors. We aimed to estimate the prevalence of stroke risk factors and identify the factors associated with metabolic risk factors in the district of Titirou, in Parakou (northern Benin) in 2016. A cross-sectional study was conducted. It included people aged at least 15 years, living in Titirou for at least 6 months, and who had given their written consent to participate in the study. A door-to-door survey was performed from 15 march to 15 July 2016 in each neighborhood until the pre-determined number was reached. Sociodemographic data, medical histories, anthropometric and blood pressure measures were recorded using the WHO STEPS approach. The prevalence of stroke risk factors was calculated, and a multivariable logistic regression was done to identify the factors associated with metabolic risk factors for stroke. A total of 4671 participants were included with a mean age of 27.7±12.9 years and a sex ratio of 0.98. Concerning the behavioral risk factors for stroke, 17.2% were alcohol consumers, 3.5% were smokers, 21.5% had low fruit and vegetable intake, and 51.1% had low physical activity practice. The prevalence of metabolic risk factors for stroke was respectively of 8.7% for obesity, 7.1% for high blood pressure, 1.7% for self-reported diabetes, and 2.2% for dyslipidemia. Age (p<0.001), sex (p<0.001), marital status (p<0.001) and professional occupation (p = 0.010) were associated with obesity. Age was also associated with high blood pressure (p<0.001) and diabetes (p<0.001). Dyslipidemia varied according to smoking (p = 0.033) and low physical activity practice (p = 0.003). The study revealed a significant prevalence of some stroke risk factors. Targeted local interventions for primary prevention of stroke should be promoted in this community.